Economic Resources and their Rotation. Emergent Qualities of the Economy - VASILYEV, Evgeny Petrovich; VASILYEVA, Zoya Andreevna; FILIMONENKO, Irina Vladimirovna; DEMCHENKO, Svetlana Kapitonovna; LIKHACHEVA, Tatyana Petrovna (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
The emergent nature of economic resources has been revealed, which determines the entire variety of processes of the initial resources consumption and restoration. An approach to determining the temporal potential of the existence of economic systems has been considered, based on their ability to self-renew their resources. The basic elements of converting some initial resource reserves to others have been determined, based on the system of preferences of individuals (their needs), which form a model for replacing the consumed initial resource reserves with restored resource reserves. It has been proved that the processes of self-renewal of the initial resource reserves are both consumption of these reserves and their restoration. As a result, all economic processes that occur in the society are presented in this article as ultimate target cycles of self-renewal of the initial reserves of all types of reproducible resources available in the economy. It has been noted that the emergent quality of the initial resource reserves (their ability to self-renew) arises only for the special matrix structure of these resource reserves. It has been established that the emergent reserve of marginal target cycles of self-renewing the initial reserves of reproducible resources in the economic system is always limited due to the division of resources into reproducible and nonreproducible. From these positions, the economic system can control the potential time of its existence, depending on the choices made by participants in economic processes. The need for the formation of a special economic mechanism aimed at maintaining and expanding the potential existence of the economic system through the development of matrix technologies for self-renewal of the initial reserves of reproducible resources is substantiated in the article. The methodological basis of the study is presented by methods of analysis and synthesis, theory of sets, and economic and mathematical modeling.